Structural model of Marital Empathy prediction based on Ego Empowerment with the mediating role of Attachment Style - Khosrobeygi, Aliasghar; Aghayousefi, Alireza; Sobhi Gharamaleki, Nasser (Applied Family Therapy Journal (AFTJ), 2021)
Aims: The aim of this study was to investigate the model of predicting marital empathy based on ego empowerment by considering the mediating role of attachment styles in married people. Method: The research method was descriptive and structural equation modeling. The statistical population of the present study was all married people who referred to health centers in Tehran in 1400. The sample size was 350 people who were selected by the available method. The sample size was 350 people who were selected by cluster sampling method. Research instruments included the My Empowerment Scale (Baron, 1953), the Marital Empathy Scale (Julif and Farrington, 2006), and the Attachment Styles Questionnaire (Hazen and Shaver, 1987). Structural equation modeling was used to analyze the data. Data analysis was performed using SPSS and AMOS statistical software. Result: The results showed that the model had a good fit in the community after eliminating a path. The results also showed that ego empowerment has a significant indirect effect on marital empathy due to attachment styles (p <0.05). This means that as the ego empowers, the level of marital empathy increases through attachment styles. Conclusion: Based on the research findings, providing appropriate strategies to improve the predictive components of ego empowerment, in order to increase the level of satisfaction and stability and stability of marriage and increase marital empathy should be considered.